STRATEGI PENINGKATAN KEPUASAN KONSUMEN JAHE SANG JAWARA DI MASA PANDEMI COVID-19 DENGAN PENDEKATAN IMPORTANCE PERFORMANCE ANALYSIS - Arif Dzulfikar; Siti Jahroh; Mochammad Mukti Ali (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
COVID-19 has major impact on human lives, the presence of this virus has made many people switch into healthy lifestyles. However, Arvan Natural Group, a start-up company which produce instant ginger Sang Jawara has not taken advantage of this opportunity optimally. Therefore, the aim of this research is to evaluate the consumer satisfaction of ginger Sang Jawara in category of product, price, promotion, and service; and formulating strategies to increase consumer satisfaction. Data collection methods used are questionnaires and in-depth interviews with selected respondents. The sampling technique used is purposive sampling with the following criteria, consumers with an age range of 20-60 years, made purchases in the last three months, knowing the promotions and benefits of the products purchased. The number of samples obtained in this study are 42 respondents. The analysis tools used are the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of the CSI analysis showed a value of 81.03%. The results of the IPA analysis show that of the 21 measurement attributes, there are 5 attributes that are suggested to experience improvement. The attributes that are in quadrant I (top priority) are the product brand, size variations, colors, and promotional bonuses. The attributes in this quadrant are suggested to be corrected immediately by the company in order to meet the expectations of consumers. Meanwhile, in quadrant III, the attribute whose performance can be improved is special attention (empathy). Keywords: COVID-19, lifestyle, IPA, instant ginger, consumer satisfaction